Potentiometric textile-based pH sensor - Zamora, Martín Lucas (2018)
Determining the pH of sweat provides valuable information for athletes and patient monitoring. This work presents a textile-based, highly sensitive pH sensor for pH determination. Three conductive fabrics (Argenmesh, Ristop silver and Sstainless steel mesh (SSM)) were modified with a pH sensitive electrodeposited iridium oxide film (EIROF). The three electrodeposited fabrics were characterized by impedance measurements. The stainless steel mesh showed the best sensitivity to pH changes and therefore was selected for further experiments. Two configurations of this fabric were evaluated, looking for improvement in pH sensitivity and temperature dependence. The best result was obtained with the configuration that maximizes the contact surface between the stainless steel fibers, showing an error of 0.15% in the pH measurement of a buffer solution. This configuration was also used to perform in vivo measurements, obtaining an error of 4% when compared to the measurements performed with a commercial pH test strip. The implementation of sensor into textiles brings some advantages such as comfort, biocompatibility and washability, among others; making the future incorporation of a sensor into a garment very possible.